Islamic Democracy or Secular? Some Aspects of Democracy Practiced in Indonesia - Brilliant Windy Khairunnisa (CV. Media Digital Publikasi Indonesia, 2023)
Indonesia is one of the largest democratic countries in the world, especially in the way of elections with its unique system. However, Indonesia is notable for its largest population of Islamic society which could influence its policy. In this regard, this study aims to analyse the democratic application in Indonesia with an Islamic democracy or secular democracy by using democracy indicators including the election process, civil liberties, government function, and political culture. This study was conducted with a qualitative explorative method while both primary and secondary data were conceived. This study results illustrate that the Indonesian state does not implement an Islamic democratic system because there is no Islamic constitution that applies in it, however, due to the existence of a majority Muslim society somehow influences some of the policies that apply therefore that it cannot be claimed to be a completely secular democracy. Nevertheless, the future of the democratic system in Indonesia will be determined by the results of the general election in 2024